Penggunaan Komputer Dalam Penulisan Notasi Muzik Di Kalangan Guru Pelatih Dari Institut Perguruan Sultan Ldris, Tanjung Malim, Perak - Abdullah, Mohd Hassan (1999)
The use of computer application in music education in Malaysia is still limited.Music teachers are not well exposed to the need for the use of computer applications. This study intends to obtain informationon the effectiveness of using computer applicationsin writing music notation among music majors enrolled in local Teachers Training Colleges.The study also intends to determine the correlation between achievement in writing music notation and level of computer literacy, as well as students' attitudes and perceptions toward computers . The study was carried out using the one group experimental method , where the subjects were given a pre-test. After they were exposed to a specific computer software as a treatment, subjects were given post-tests to measure their achievement in writing music notation,attitudes and perception stoward computers and computer literacy levels.All the data gathered fro m these tests were analysed using t-test method a n d Pearson's Correlation.